Resenha de Balzer, Wolfgang, Moulines, C. Ulises e Joseph Sneed, Una arquitectónica para la ciencia. El programa estructuralista, Quilmes: Universidad Nacional de Quilmes, 2012, 498 pp. Tradução de Pablo Lorenzano. - Abreu, Cláudio (Metatheoria – Revista de Filosofía e Historia de la Ciencia, 2012)
This is the review written by Cláudio Abreu of Pablo Lorenzano’s Spanish translation of An Architectonic for Science. The Structuralist Program by Wolfgang Balzer, C. Ulises Moulines and Joseph D. Sneed.